Analisis efisiensi usaha peternakan ayam ras pedaging pola inti-plasma di Kabupaten Magelang - Izati, Isna Hana Nur; Laut, Lorentino Togar; Panjawa, Jihad Lukis; Prakoso, Jalu Aji (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
This study aims to analyze the factors of production on chicken meat production, analyze the level of business efficiency and inefficiency in broiler farms, and analyze what factors influence the level of technical efficiency of the broiler farming business in Magelang Regency. This study uses primary data collected in the period June-October 2022 using the Cluster Random Sampling method. The production factor variables used in this study are capital per period, DOC (Day Old Chick)/chicks, feed, drug units, and labor with the dependent variable being the production of chickens in kilograms. While the inefficiency variables are age, education, gender, experience, number of family dependents, number of visits, Feed Conversion Ratio (FCR), chicken mortality, and cage density. Research findings show that all production factors have a positive impact on increasing chicken production results for broiler farmers. The results of the calculation, it was found that of the 81 breeders, the lowest efficiency value was 60 percent while the highest efficiency value was 97 percent with an average efficiency of 88 percent, which means that there is still a potential of 12 percent to be developed. Thus, there is still potential to restore the position of broiler farming as a base sector. Therefore, the government's role is very important to restore the broiler farming business in Magelang Regency so that it becomes a base sector.